Preventive Effects of Phenolic Compound Extra Virgin Olive Oil (EVOO) on the Incidence of Hand Foot Syndrome Induced Capecitabine - Yenny Dian Andayani; Mgs Irsan Saleh (HM Publisher, 2022)
Hand foot syndrome (HFS) is a reaction that occurs on the skin of the palms and soles. feet, caused by the toxicity of chemotherapy drugs with symptoms such as tingling, pain, erythema, dry skin, swelling, increased pigmentation and itching. This condition is still a problem in the treatment of patients given capecitabine. Although HFS does not cause death, in severe cases it can affect the quality of treatment and interfere with daily activities. The cause of HFS is still unclear but from research it is known that capecitabine and its metabolites will increase the expression of the COX-2 enzyme, inhibit the arachidonic pathway, increase PGE2 activity, causing inflammatory reactions in the form of erythema, edema and pain. The phenolic components contained in EVOO, namely oleocanthal and hydroxytyrosol compounds in several studies have the same properties as celecoxib and ibuprofen as anti-COX-2, will inhibit the arachidonic synthesis pathway, reduce prostaglandin activity and reduce inflammatory reactions.